Dynamic tension–compression asymmetry of martensitic transformation in austenitic Fe–(0.4, 1.0)C–18Mn steels for cryogenic applications. (1st September 2015) - Kim, Hyunmin; Park, Jaeyoung; Ha, Yumi; Kim, Wooyeol; Sohn, Seok Su; Kim, Hyoung Seop; Lee, Byeong-Joo; Kim, Nack J.; Lee, Sunghak
Abstract: In this study, cryogenic-temperature dynamic mechanical properties of austenitic Fe–(0.4, 1.0)C–18Mn steels were evaluated by conducting dynamic tensile and compressive tests, and deformation mechanisms including tension–compression asymmetry of martensitic transformation behavior were interpreted by microstructural evolution of dynamically tensioned or compressed specimens. After the dynamic tensile test of the 0.4C–18Mn steel, the γ → ɛ → α ′ martensitic transformation occurred at −196 °C, whereas ɛ - or α ′-martensite was not found in the 1.0C–18Mn steel. After the dynamic compressive test, on the other hand, the γ → ɛ martensitic transformation occurred at −196 °C without the formation of α ′-martensites in the 0.4C–18Mn steel. This dynamic tensile-compressive asymmetry of martensitic transformation was plausibly interpreted by austenite stability in relation with difference in molar volume, hydrostatic stress distribution, and adiabatic heating. The γ → α ′ transformation was prevented under the dynamic compressive loading because the increase in molar volume was required for the γ → α ′ transformation, whereas it was promoted to induce the γ → ɛ → α ′ transformation under dynamic tensile loading.